282 HELMET USE DOCUMENTATION PRE- AND POSTINJURY DOCUMENTATION SHEET. (1st January 2006) - Bates, R.; Hunter, J.; Meredith, M.; Nichols, M. H.; King, W. D.; Monroe, K. W.
Abstract : Background: Previous studies have shown that routinely completed free text emergency department (ED) medical records contain limited information necessary for injury surveillance. We instituted an injury documentation sheet into our ED records to evaluate impact on documentation rates. Methods: The pretest/post-test study design used ICD9 codes to identify bicycle-related injuries. A standardized data collection tool was utilized to review these charts. Time periods before and after institution of a standardized documentation sheet were reviewed. Period 1 was January until December 2004. Period 2 was January until June 2005. Data were entered into Epistat and Z scores were used for comparison. Results: Initial review (n = 667) revealed mean age of patient 8.6 years with 46% African American and 67% male. Helmet usage was documented in 49% of charts (81 were wearing helmets, 245 were not wearing helmets). Mechanism of injury was documented as bike alone in 587, bike vs car 13 and bike vs stationary object 64. After implementation of an injury data sheet: n = 205; mean age was 9.24 with 51% African American and 43% male. Helmet use was documented in 77% of cases (26 wearing helmets; 132 not wearing). Mechanism was documented as bike alone 180; bike vs car 96 and bike vs stationary object 20. Helmet use was much more frequently documented after the initiation of an injury documentation reminder sheet (z = 6.97; p < .001 95% CI 20.2, 35.8). Conclusion: Documentation is improved with the use of standard injury documentation prompts. Routine use of reminders vastly improves documentation rates.